Pelaksanaan Metode Demonstrasi Dalam Pembelajaran Haji Pada Kelas Ix Di Smp Negeri 7 Surakarta Tahun Pelajaran 2015/2016 - Kurniawan, Aditya Rully; , Drs. Najamuddin Zuhdi, M. Ag (2017)
ABSTRACT Currently active learning methods is very interested in the learning process, because it simplifies teachers in presenting the subject matter and may be an attempt to make students active in the classroom. One method of active learning that is often used is the demonstration. This method is suitable for practice learning, one of which is learning the h}ajj. Materials include learning material that can not be presented directly in front of students, because of the time and place of execution have been specified. Thus, in the implementation of learning required h}ajj appropriate methods to make students understand the material. Therefore this study examines The Implementation of The Demonstration Methods in Teaching H}ajj in Class IX in SMP Negeri 7 Surakarta in academic year 2015/2016, with the formulation of the problems: (1) How is the implementation of the demonstration method in teaching h{ajj in class IX students at SMP Negeri 7 Surakarta in academic year 2015/2016; (2) To which extent is the benefit of the implementation of the demonstration method in teaching h{ajj in class IX SMP Negeri 7 Surakarta in academic year 2015/2016. Meanwhiles the aim is (1) to describe the implementation of the demonstration method in teaching h}ajj in class IX students at SMP Negeri 7 Surakarta in academic year 2015/2016, and (2) to describe the benefit of the implementation of the demonstration method in teaching h}ajj in class IX SMP Negeri 7 Surakarta in academic year 2015/2016. This research is a field research by means of qualitative approach which requires the author to jump directly in the empiri and interact directly to obtain valid and accurate data as needed. These data collection uses interview and documentation. While technical analysis of the data uses descriptive qualitative and inductive method, i.e the pattern of reasoning that begins by presenting the statements that have a unique scope and limited in formulating arguments and ends with the conclusion of a general nature. The results of this study indicate that (1) implementation of demonstration method in teaching h}ajj has been held in order to introduce procedures for the pilgrimage to the students; (2) carried at asrama haji Donohudan on 12 December 2015; and (3) the benefits of the implementation of the demonstration method in teaching h{ajj include: (a) Students can understand and absorb a lesson well; (b) Impact both on the enthusiasm of student learning, because in addition to learning they also feel the atmosphere of recreation; (c) students feeling of happiness to their school, because h{ajj menasik is held outside of school, and; (d) development of the desire and enthusiasm among the students to perform h}ajj and umrah. Keywords: Method demonstrations, Learning h{ajj, SMP Negeri 7 Surakarta